Nyt AI-værktøj til det teologiske laboratorium? Didaktiske refleksioner over et forsøg med brug af Transkribus til undervisning i kirkehistorie - Nissen, Nanna Eva; Reeh, Tine Ravnsted-Larsen (Kirkehistoriske Samlinger, 2025)
This article presents an experiment involving the inclusion of new digital tools for reading handwritten sources in the teaching of church history at the undergraduate level at the Faculty of Theology in Copenhagen during the autumn semester of 2022. The article begins by linking the experiment to the university’s objective of providing research-based education at the highest international level, while also tracing back to the Faculty of Theology’s earlier efforts to update the form and content of teaching with the establishment of a Theological Laboratory in 1903. Following this, the article presents more general considerations about research-based teaching that form the basis for the experiment, including existing views and models for integrating research into university teaching. Next, the article focuses on the execution of the experiment, emphasising the pedagogical and practical considerations of using a new tool in teaching. As a counterbalance to the teacher’s perspective, the student perspective is presented through three focused interviews in which three selected students describe their experiences of working with the handwritten sources. The article concludes with a reflection on the benefits and challenges of the experiment, emphasising the need for differentiated teaching where students can engage with the new digital tools and the challenging handwritten sources to an extent that suits their individual motivation and level.